2021
DOI: 10.3390/cancers13133116
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Proteomic Analysis in Non-Small Cell Lung Cancer Patients Treated with PD-1/PD-L1 Blockade

Abstract: Checkpoint inhibitors have been approved for the treatment of non-small cell lung cancer (NSCLC). However, only a minority of patients demonstrate a durable clinical response. PD-L1 scoring is currently the only biomarker measure routinely used to select patients for immunotherapy, but its predictive accuracy is modest. The aim of our study was to evaluate a proteomic assay for the analysis of patient plasma in the context of immunotherapy. Pretreatment plasma samples from 43 NSCLC patients who received anti-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 50 publications
2
22
0
1
Order By: Relevance
“… 43 CXCL10 was identified as a biomarker for response as well. 44 In addition, previous studies have demonstrated an association between these two chemokines and resistance to therapy in patients with NSCLC. Oyanagi et al reported significantly lower baseline levels of CXCL8, CXCL10 and tumor necrosis factor-α and higher levels of follistatin in patients with durable response.…”
Section: Discussionmentioning
confidence: 98%
“… 43 CXCL10 was identified as a biomarker for response as well. 44 In addition, previous studies have demonstrated an association between these two chemokines and resistance to therapy in patients with NSCLC. Oyanagi et al reported significantly lower baseline levels of CXCL8, CXCL10 and tumor necrosis factor-α and higher levels of follistatin in patients with durable response.…”
Section: Discussionmentioning
confidence: 98%
“…CXCL9 and CXCL10 have previously been reported to be increased in plasma following treatment with PD-1 blockade in patients with non-small-cell lung cancer, and this was associated with longer PFS. 32 In the current trial, we found that, while CXCL9 and CXCL10 were increased after treatment, these were not associated with longer treatment time or rPFS. In contrast, increases in IFN-γ were, suggesting that T-cell activation, presumably by vaccination, which may be important to improving the efficacy Open access of 1 blockade.…”
Section: Discussionmentioning
confidence: 45%
“…In such testing, it is important to consider how genomic and proteomic data can be optimally paired to maximize potential predictive utility as gene expression of secretory proteins does not always translate to similar changes in protein expression, and vice versa 8,74 . For this reason, measuring circulating plasma protein measurements before and after anti-PD-L1 treatment in patients using multiplex immunoassay and proximity extension assays as a standardized assessment across studies may be considered to provide more consistent results [75][76][77] .…”
Section: Discussionmentioning
confidence: 99%